Memahami Penggunaan dan Motivasi Akun Anonim Instagram di Kalangan Remaja - Nosiva Rini, Lilis; Manalu, S. Rouli (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
This research based on the increasing popularity of multiple accounts consisted of real and anonymous accounts on Instagram among teenagers. Anonymity involved various aspects that generate both positive and negative effects because of the vagueness of an anonymous account. The vagueness of the anonymous account varied between freedom of expression to cyberbullying. The purpose of this research is to analyze the difference between the usage of real and anonymous account as well as the motivation behind the anonymous account. This qualitative descriptive research uses a post-positivist paradigm and content analysis to compare the anonymous and real account of Instagram. Followed by an in-depth interview to understand the experience and motive to use an anonymous account. The concept of Online Disinhibition Effect applied in this research to see positive and negative behavior behind the use anonymous account. The findings show that the anonymity that exists in teen anonymous accounts is not full anonymity, but pseudonym account instead. This pseudonym account becomes an arena for the creation of identity by choosing an identity that is considered to have a certain meaning. However, on anonymous accounts the uploaded content has varied tones namely happy, sad, annoyed tones, compared to the real account which is only dominated by happy tones. In addition, it was found that the reason teens use anonymous accounts because of freedom of expression including better self-disclosure, avoiding mixing of content displayed by Instagram algorithm, protecting privacy on the real account, and as a opportunity for cyberstalking another Instagram users.